Malignant transformation arising from mature ovarian cystic teratoma: A case series. Issue 13 (2nd April 2021) - Qin, Li; Zhao, Tao; Liu, Xin; Wang, Hongli; Gu, Xin; Chen, Dian; Wang, Zaiping; He, Du
Abstract : Abstract: Malignant transformation arising in mature cystic teratoma (MT-MCT) is a rare neoplasm of the ovary. Herein, we aimed to evaluate the clinicopathological features and treatment outcome of the Han Chinese women with MT-MCT. In this retrospective study, the clinical data of patients who had been surgically treated from January 2000 to November 2019 and in whom the diagnosis of MCT was confirmed based on the pathology were included. Fourteen patients with MT-MCT from a total of 569 cases (2.46% incidence) of MCT were reviewed. The mean age of patients with MT-MCT was 51.3 (range, 31–71) years, while the mean age of patients with MCT was 45.3 (range, 17–62) years. Upon gross examination, the mean size of MT-MCT was 14.0 (range, 11–25) cm, whereas the mean size of MCT was 7.5 (range, 4–10) cm. Primary surgical staging was performed in all cases. Complete cytoreduction and suboptimal surgical resection were performed in 12 (85.7%) and 2 (14.3%) cases, respectively. Thirteen patients with malignant transformation of squamous cell carcinoma (SCC) whose Federation International of Gynecology and Obstetrics stage was >1 received chemotherapy, comprising carboplatin and paclitaxel. Response to the chemotherapy regimen was complete in 12 patients; 1/12 patients died within the median follow-up period of 16.5 months. The 5-year overall survival rate and disease-free survival rates were 31.2% and 31.6%, respectively. From the data generated, we conclude that the rate of MT-MCT increases with age. The MT-MCT was much higher in women of postmenopausal age than in younger women. We described our experience of successfully treating patients with malignant transformation of SCC with primary surgical staging and adjuvant chemotherapy (cisplatin, paclitaxel, bleomycin, and etoposide) that might improve survival in patients with advanced-stage disease.